Efektivitas Pupuk Organik Cair Limbah Jerami Padi dan Batang Pisang Terhadap Pertumbuhan dan Kandungan Fosfor Tanaman Sawi Hijau (Brassica juncea L.) - Andria Putri; Aminah Asngad (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
The research aims to determine the effectiveness of the growth and phosphorus (P) content of green mustard plants (Brassica juncea L.) after administering POC from rice straw waste and banana stems at different time intervals and doses. The research method used was an experiment with a Completely Randomized Design (CRD) type of two factors, including the dose of liquid organic fertilizer (D1 = 10 ml and D2 = 13 ml) and the time interval for fertilizer application (I1 = once 5 days and I2 = once 7 days) and 3 repetitions. The results were analyzed using a two-way ANOVA with a significance level of 0.05. The results showed that the treatment given had a significant effect on the growth of plant height, wet weight, root length, and phosphorus content but had no significant effect on the growth of the number of leaves. I1D1 treatment (5 day interval, dose of 10 ml) is the best treatment for plant growth and phosphorus content of green mustard greens (Brassica junea L.). Keywords: Mustard Greens, Rice Straw, Banana Stems, Liquid Organic Fertilizer, Growth, Phosphorus